2022
DOI: 10.1242/dev.200870
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial respiration and dynamics of in vivo neural stem cells

Abstract: Neural stem cells (NSCs) in the developing and adult brain undergo many different transitions, tightly regulated by extrinsic and intrinsic factors. While the role of signalling pathways and transcription factors is well established, recent evidence has also highlighted mitochondria as central players in NSC behaviour and fate decisions. Many aspects of cellular metabolism and mitochondrial biology change during NSC transitions, interact with signalling pathways and affect the activity of chromatin-modifying e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 132 publications
0
3
0
Order By: Relevance
“…We find that tectal NPCs, like cortical NPCs have abundant mitochondria that distribute throughout the cells (Figs 1-3), which is striking given that proliferating cells do not to generate ATP (Agathocleous et al, 2012;Petridi et al, 2022). The elongated, polarized NPCs are unique brain cells in that their cell bodies or apical endfoot physically interfaces with inner ventricle of the brain, but they also contact the outer surface though interactions of their pial endfeet with vasculature and the developing meninges.…”
Section: Mitochondria Distribution and Movements In Tectal Npcsmentioning
confidence: 74%
See 1 more Smart Citation
“…We find that tectal NPCs, like cortical NPCs have abundant mitochondria that distribute throughout the cells (Figs 1-3), which is striking given that proliferating cells do not to generate ATP (Agathocleous et al, 2012;Petridi et al, 2022). The elongated, polarized NPCs are unique brain cells in that their cell bodies or apical endfoot physically interfaces with inner ventricle of the brain, but they also contact the outer surface though interactions of their pial endfeet with vasculature and the developing meninges.…”
Section: Mitochondria Distribution and Movements In Tectal Npcsmentioning
confidence: 74%
“…Stem cells actively regulate mitochondrial structural dynamics and mitochondrial inheritance. Therefore, it is surprising that across tissues and organisms stem cells do not require or, indeed, actively inhibit gene expression and metabolic processes that require mitochondria (Angelopoulos et al, 2022;Khacho et al, 2019;Petridi et al, 2022). For brain stem cells, the reliance on non-mitochondrial ATP production was first shown in vivo by Agathocleous et al (2012) who found that despite having mitochondria and oxygen, neural progenitor cells of Xenopus laevis retina preferentially used glycolysis, a non-mitochondrial mechanism for generating ATP.…”
Section: Introductionmentioning
confidence: 99%
“…During embryonic development, neuronal stem cells are mitotic and actively proliferate to support brain growth. 57 , 58 , 59 The mitosis of neuronal stem cells is important for the proper regulation of cell fate determination in the developing brain. 58 , 59 , 60 At the same time, neuronal stem cells differentiate into specific types of neurons and glial cells in neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“… 57 , 58 , 59 The mitosis of neuronal stem cells is important for the proper regulation of cell fate determination in the developing brain. 58 , 59 , 60 At the same time, neuronal stem cells differentiate into specific types of neurons and glial cells in neurogenesis. 57 , 58 , 59 It is possible that the mitotic regulation of mitochondrial division is crucial in such neuronal stem cells for proper neurogenesis and thereby establishing neural circuits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation